Corrosion resistance of AISI 316L plasma nitrided at different temperatures and times - Olzon-Dionysio, Maristela; Olzon-Dionysio, Danilo; Campos, Marcelo [UNESP]; Shigeyosi, Willian Takemitsu; de Souza, Sylvio Dionysio; de Souza, Solange (Springer Nature, 2019)
Austenitic stainless steels are widely used as biomaterial and corrosion resistance is one of the most important characteristics in determining the suitability of a material for this purpose. Plasma nitriding is a surface treatment that introduces interstitial nitrogen into these steels, which improves this property as a result of the nitrided layer, whose properties depend strongly on the conditions used in the process. In this paper, the nitriding temperatures (623, 673 and 723 K) and times (3, 4 and 5 h) were investigated. The Mössbauer Spectroscopy was correlated to the corrosion results with the purpose of finding the combination of time and temperature that optimize the corrosion improvement. An alternative method of spectra analysis, which analyzes qualitatively the hyperfine magnetic field distributions, was used and showed that the nitrided layer protects against corrosion, not only because of the expanded austenite, but also, and mainly, because of the nitrides, which are formed therein, located up to a depth of 0.1 μm. Moreover, these results indicate that temperature = 673 K and time = 4 h is the most efficient combination to optimize the corrosion resistance of the samples, nitrided at 6 Torr of the 80% H 2 –20% N 2 gas composition. They also confirm that corrosion protection increases for higher nitriding pressure.
Keywords: AISI 316L; Corrosion resistance; Mössbauer spectroscopy; Plasma nitriding